ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN SISWA DI LEMBAGA PENDIDIKAN PENGEMBANGAN PROFESI INDONESIA (LP3I) POTENSIA PALEMBANG - Azizah; Telly Pauline Ulviana Siwi (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
Lembaga Pendidikan dan Pengembangan Profesi Indonesia (LP3I) Palembang Potensia is an educational institution that aims to provide good service to its customers. In this study looked at the effect of service quality on student satisfaction at the Lembaga Pendidikan dan Pengembangan Profesi Indonesia (LP3I) Palembang. Based on the calculation of the Community Satisfaction Index that refers to KEPMENPAN Number KEP / 25 / M.PAN / 2/2004, an index number of 35.00 is obtained at intervals of 20.00 - 40.00. Based on the service quality index, the service quality of the Lembaga Pendidikan dan Pengembangan Profesi Indonesia (LP3I) Potensia is at the level of